Prevalence and detection of SARS-CoV-2 by RT-PCR: an analytical study - Lekha Tuli, Lekha Tuli; Shariq, Mohd; Patawa, Rohit (Journal of Ideas in Health, 2024)
Background: The COVID-19 pandemic has significantly affected the healthcare system. RT-PCR has played a major role in the confirmation of SARS-CoV-2 thus helping in an early diagnosis, clinical interventions and patient isolation. This study was conducted to ascertain the importance of RT-PCR testing among symptomatic and asymptomatic cases in different age groups with association to infection. Methods: This retrospective cohort study was conducted from August 2020 to August 2021, in the Department of Microbiology, Autonomous State Medical College and Sarojini Naidu Memorial Hospital, Firozabad, Uttar Pradesh, India. Samples were collected from a total of 342, 281 cases which comprised of symptomatic patients (ILI, SARI), asymptomatic contacts, those seeking hospitalization, travelers and were subjected to testing by RT-PCR. The cases were divided into group A of patients presenting with symptoms ≤7 days, group B of patients with signs and symptoms >7 days and group C comprised of asymptomatic cases. The symptoms of patients were associated with the Ct values of the E/N screening gene and the RdRp/ORF1ab confirmatory genes. The Chi-square test was done to test the statistical significance of association of symptomatic patients with the outcome of the test. Results: The number of positive samples were 4,342 showing a prevalence of 1.3%. The maximum prevalence of infection was found in the age group of 20-29 years followed by the age group 30-39 years (p-value <0.05). The maximum positivity and high viral load were seen in the patients who presented with symptoms ≤7 days with Ct values ≤25. Conclusion: The maximum infection was found in the young age group. The screening and confirmatory genes could be detected in the samples of asymptomatic cases also which was helpful in isolating them and breaking the chain of further spread of the virus.